A Tale of Two Conditions: Pediatric Brugada Syndrome Unveiled—Navigating the Challenges of Coexisting Arrhythmia and Fever‐Induced ECG Pattern - Hei‐To Leung; Sit‐Yee Kwok; Fong‐Ying Shih; Kin‐Shing Lun; Tak‐Cheung Yung; Sabrina Tsao (Annals of Noninvasive Electrocardiology)
ABSTRACT Background Brugada syndrome (BrS) is an inherited channelopathy characterized by right precordial ST‐segment elevation. This study investigates the clinical and genetic characteristics of children with BrS in Hong Kong. Methods A retrospective review was conducted at the only tertiary pediatric cardiology center in Hong Kong from 2002 to 2022, including all pediatric BrS patients under 18 years old. The diagnosis of BrS was established with a type 1 ECG pattern detected spontaneously or induced by flecainide, excluding secondary causes. Results Eight probands of mean age 10 years old were identified. Male dominance was observed (6 boys vs. 2 girls). The mean follow‐up duration was 4.6 years (Median 3.5 years). Patients had type 1 ECG pattern either spontaneously (n = 4) or provoked by flecainide (n = 4). Fever was present in seven patients at the initial presentation, and two patients experienced aborted cardiac arrest and one had symptomatic ventricular tachycardia. All symptomatic patients received implantable cardioverter‐defibrillator placement. Five asymptomatic patients (62.5%) were diagnosed with BrS through ECG during febrile illness, and they remained asymptomatic following conservative management involving strict fever control and medication avoidance. Two patients with mixed phenotype (one with long QT syndrome and another with ectopic atrial tachycardia) required antiarrhythmics and one patient received transcatheter ablation for atrial tachycardia to achieve optimal arrhythmia control. Conclusion Fever plays a significant role in unmasking BrS in children. Asymptomatic children with BrS managed conservatively have a favorable prognosis. Difficult arrhythmia control was found in patients with mixed phenotype.